Latino men's qualitative perspectives on a lay health advisor intervention to promote their sexual health. (5th December 2014) - Wagoner, Kimberly G.; Downs, Mario; Alonzo, Jorge; Daniel‐Ulloa, Jason; Rhodes, Scott D.
Abstract Lay health advisor (LHA) approaches are a promising strategy to reduce health disparities among communities considered 'hard to reach' by researchers and practitioners. LHAs have addressed a variety of health issues, but limited studies have included men as LHAs. The purpose of this study was to better understand the roles of male LHAs and their male‐helping relationships. We used an inductive approach to explore Latino men's perspectives on serving as LHAs for other Latino men and Latino men's views on receiving sexual health information from a male LHA. We collected qualitative data in 2009 and 2010 as part of an LHA intervention designed to reduce the risk of HIV infection among immigrant Latinos through the social networks of soccer teams. We analysed and interpreted data from 30 in‐depth interviews with Latino men who served as LHAs and their social networks in North Carolina, USA. Participants shared perceptions on social network importance for immigrant Latinos, facilitators and challenges of helping other men, recommendations for intervention modification and suggestions for future work involving the Latino community. Findings revealed that Latino men are receptive to fulfilling the roles of health advisors and opinion leaders, and can effectively serve as LHAs. Social network members valued the social support they received. Working through sports teams and identifying existing leaders to be LHAs may be a culturally congruent approach to meeting Latino community needs. More research is needed on the potential of male LHAs to address other health issues.